2019
DOI: 10.3389/fimmu.2019.02797
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2: Its Potential Role and Regulatory Mechanism in Host Immune Response in Diseases

Abstract: Sestrin2 (SESN2), a highly evolutionarily conserved protein, is critically involved in cellular responses to various stresses. SESN2 has a protective effect on physiological and pathological states mainly via regulating oxidative stress, endoplasmic reticulum stress, autophagy, metabolism, and inflammation. In recent years, breakthrough investigations with regard to the regulation and signaling mechanisms of SESN2 have markedly deepened our understanding of its potential role as well as its significance in hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 123 publications
0
44
0
Order By: Relevance
“…Although we did not confirmed the Sesn2 interaction with TRAF6 or p62 under RANKL-induced osteoclast differentiation, our results combined with previous reports suggest that Sesn2 promotes a strong interaction between TRAF6 and p62 and promotes RANKL-induced osteoclastogenesis via activations of NF-κB and MAPK downstream signaling pathways. In addition, to protect cells against endotoxicity, such as inflammation and aging, Sesn2 is activated by an increase in oxidative stress-induced Nrf2 and AP-1 via activation of toll-like receptors, by inhibition of ubiquitin-mediated Sestrin degradation, and by an increase in Sestrin-MAPK complexes in immune cells ( Wang et al, 2019 ; Kim et al, 2020 ). Further, it has been shown that p62 is highly expressed in osteoclasts in periapicitis and periodontitis models and that NOX4 is highly expressed in bones obtained from patients with osteoporosis and Paget disease, a focal disorder of enhanced bone remodeling ( Goettsch et al, 2013 ; Li et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not confirmed the Sesn2 interaction with TRAF6 or p62 under RANKL-induced osteoclast differentiation, our results combined with previous reports suggest that Sesn2 promotes a strong interaction between TRAF6 and p62 and promotes RANKL-induced osteoclastogenesis via activations of NF-κB and MAPK downstream signaling pathways. In addition, to protect cells against endotoxicity, such as inflammation and aging, Sesn2 is activated by an increase in oxidative stress-induced Nrf2 and AP-1 via activation of toll-like receptors, by inhibition of ubiquitin-mediated Sestrin degradation, and by an increase in Sestrin-MAPK complexes in immune cells ( Wang et al, 2019 ; Kim et al, 2020 ). Further, it has been shown that p62 is highly expressed in osteoclasts in periapicitis and periodontitis models and that NOX4 is highly expressed in bones obtained from patients with osteoporosis and Paget disease, a focal disorder of enhanced bone remodeling ( Goettsch et al, 2013 ; Li et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sesn2, an antioxidant, activates AMP-activated protein kinase (AMPK) and inhibits mTORC1 signaling. Sesn3 also suppresses mTORC1 activity and maintains Akt activity by activating the AMPK-TSC1/2 signaling axis ( Wang et al, 2019 ; Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that overexpression of SESN2 inhibited both expression of N-cadherin and activation of p70S6K. The anti-cancer effects of SESN2 are associated with regulation of the mTORC1 signaling pathway [ 58 , 59 ]. The mTOR signaling pathway is hyperactivated during carcinogenesis and tumor progression [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sestrin2, a highly evolutionarily conserved protein, is involved in mediating cellular responses to various stressors. It has a protective effect against physiological and pathological conditions, mainly through regulating oxidative stress and inflammation [35]. Sestrin2 is a leucine sensor protein that regulates mTORC1 signaling that is related to cell proliferation and growth.…”
Section: Discussionmentioning
confidence: 99%